Sustainable Interior Design - Bullock, Chloe (London : RIBA Publishing, 2024)
What does it mean to be a sustainable interior designer? Where do you start? This book demystifies how to be a sustainable interior designer, both within practice and on design projects. It gives you the tools to educate clients that sustainable practice isn't necessarily more expensive, and what the options available to them are in terms of design concept, materials and finishes. Importantly, the book also looks at sustainable supply chains, particularly important when specifying FF+E. Where to start being sustainable can be a difficult decision. Acting as a primer for interior designers at any stage of their career, it outlines what you really need - and don't need - to know. Inspirational case studies from around the world sit alongside crucial guidance on the benefits of being sustainable and how to work with enlightened clients. There is information on how sustainable design contributes to health and wellbeing, all backed up by authoritative best practice guidance.
About the Author & Acknowledgements1. Introduction2. Reuse3. Circular Economy4. Sharing Economy5. Regenerative Design6. Vegan Design7. People8. Place9. Biophilic Design10. Healthy Building11. Climate and Biodiversity Emergency12. Ethical BusinessIndexImage Credits
"RIBA Publishing"
Keywords: Interior decoration; Sustainable living; ARCHITECTURE / Interior Design / General; ARCHITECTURE / General